Photophysical Behaviour of p-Dihydroxy Benzene in Different Solvents, pH and a-Cyclodextrin - Prema Kumari, J.; Allen Gnana Raj, G. (Asian Journal of Chemistry, 2010)
Spectral characteristics of p-dihydroxy benzene have been studied in different solvents, pH and a-cyclodextrin. Solvent study shows that the interaction of -OH group with the aromatic ring is less than that of -NH2 group both in the ground and excited states. In absorption, the charge transfer interaction of -OH group in p-position is larger. pH studies reveals that p-dihydroxy benzene is more acidic than phenol. p-Dihydroxy benzene forms a 1:1 inclusion complex with a-cyclodextrin. In a-cyclodextrin medium, absorption spectra of p-dihydroxy benzene shows unusual blue shift, whereas in the excited state, the spectral charac-teristics of p-dihydroxy benzene follow the same trend in both aqueous and a-cyclodextrin medium. The inclusion complex of a-cyclodextrin with p-dihydroxy benzene is investigated by UV-visible and fluorimetry and scanning electron microscope.